Multiple‐Dose Pharmacokinetics, Safety, and Tolerability of Aprocitentan, a Dual Endothelin Receptor Antagonist, in Healthy Japanese and Caucasian Subjects - Fontes, Magda S.C.; Dingemanse, Jasper; Sidharta, Patricia N. (Clinical pharmacology in drug development, 2021)
Aprocitentan is an orally active dual endothelin receptor antagonist currently in development for treatment of difficult‐to‐control (resistant) hypertension. In phase 1 and 2 studies, aprocitentan has been characterized predominantly in Caucasian subjects. In this bridging, double‐blind study, 20 healthy Japanese and Caucasian male and female subjects received 25 mg of aprocitentan or placebo once daily for 10 days and were monitored until 216 hours after the last dosing. The pharmacokinetics of aprocitentan were similar between ethnicities. At steady state, maximum plasma concentration was reached at 4 and 3 hours, and elimination half‐life was 49.1 and 48.8 hours for Japanese and Caucasian subjects, respectively. The accumulation index was around 3 for both populations. Geometric means ratios for maximum plasma concentration and area under the plasma concentration–time curve during 1 dosing interval were around 1, with 90% confidence interval ranging from 0.87 to 1.30. Aprocitentan was safe and well tolerated in both groups. As no clinically relevant differences were found between Japanese and Caucasian subjects, it is unlikely that the pharmacokinetics of aprocitentan would differ significantly between Caucasian subjects and other ethnicities. Aprocitentan can therefore be administered at a dose level of up to 25 mg in any ethnicity without dose adjustment.